Yeast diversity in the oral microbiota of subjects with periodontitis: Candida albicans and Candida dubliniensis colonize the periodontal pockets - Urzúa, B; Hermosilla, G; Gamonal, J; Morales-Bozo, I; Canals, M; Barahona, S; Cóccola, C; Cifuentes, V (Medical mycology (Oxford), 2008)
The term periodontitis encompasses several polymicrobial infectious diseases, of multifactorial etiology, with chronic and aggressive forms. In spite of the etiopathogenic differences between these two forms of the disease, few studies have analyzed the subgingival colonization by yeast. The objective of this investigation was to analyze the composition of the yeast microbiota present in the mucosa and subgingival sites of healthy individuals and patients with aggressive and chronic periodontitis. For this, samples were recovered from these two locations and the yeast recovered identified by phenotypic and genotypic methods. Patients with chronic periodontitis showed significant differences in relation to the other groups with respect to carrier status (69.2% versus 35.7% of healthy individuals; [chi(i)(2) test; p=0.014]), the total number of isolated colony forming units or CFU (mean and ranges 281.6 (0-6048) [K-W(2)=6.998; p=0.03]), the Simpson diversity index (I) in site b (I(b)=0.344 versus healthy subjet and aggresive periodontitis where I=0 [multiple t-test comparisons with the Bonferronni correction, p<0.05]), and the species profile. Interestingly, in spite of the varied profiles of the species present in the mucosa of the three groups analyzed we noted that only C. albicans and C. dubliniensis were capable of colonizing the periodontal pockets in patients with chronic periodontitis, while only C. albicans was identified in the subgingiva of healthy individuals and patients with aggressive periodontitis.